Improvement of the mechanism for evaluating enterprise performance efficiency - Zhengjie, Li (Харківський національний автомобільно-дорожній університет, 2025)
The paper analyzes the existing approaches to assessing the effectiveness of activities, studies the results of the activities of Transport Consulting LLC and develops a methodological approach to improving this process based on the use of the matrix method. Recommendations for improving the efficiency of Transport Consulting LLC are proposed, their potential consequences for the activities of the enterprise are assessed. Prospects for further research are defined as an analysis of the impact of "green" technologies on the environmental sustainability of logistics processes and the expansion of the use of improved assessment methods in the context of globalization.
Keywords: performance evaluation; enterprise activities; performance management; sustainable development